Variable selection for linear regression: forward selection vs least angle regression (Bangladesh Journal of Scientific Research, 2011)
Key words: Forward selection; Least angle regression; Linear regression; Stepwise procedureBangladesh J. Sci. Res. 23(1): 39-48, 2010 (June)